Perfil funcional e repertório ocupacional de crianças típicas e crianças diagnosticadas com transtorno do espectro autista - Faustino, Gabriela Fernanda (2022)
As in other life cycles, childhood is also characterized by specific occupations. It is through the performance of occupations that children constitute their occupational repertoire. Considering that delays or functional losses are factors that can hinder the performance of an occupation, neurodevelopmental disorders influence the composition of the occupational repertoire to the extent that they interfere with functionality. Although Autism Spectrum Disorder (ASD) is the most common neurodevelopmental disorder today, there are no studies in Brazil on the development of the occupational repertoire of this population. Therefore, the present study aimed to investigate the functional profile and occupational repertoire of children between 2 and 12 years of age, both with typical development and diagnosed with Autism Spectrum Disorder (ASD) through the following instruments: Pediatric Disability Assessment Inventory - Testing Adaptive Computing (PEDI-CAT) and Occupational Repertoire Development Measure – Parent (ORDM-P). This is a cross-sectional and descriptive study with a quantitative approach. The sample consisted of 40 mothers of children between 2 and 12 years of age, from and residing in the state of São Paulo. Of these, 20 were mothers of typically developing children, and 20 were mothers of children diagnosed with ASD. The children were evaluated using the PEDI-CAT to identify their functional profile and the ORDM-P to characterize their occupational repertoire. As for the functional profile of children with typical development, the results obtained by the PEDI-CAT, indicated that of the 20 children who composed the Typical Group, all obtained normative scores within a normal range for their age group in the four areas evaluated by the instrument. In contrast, in the ASD Group, 10 of the 20 children had normative scores below expectations in at least one of the areas. The development of the occupational repertoire of children in the Typical Group showed similarities in the composition and acquisition of activities according to age groups, varying in relation to the predominance of some occupations in the children's repertoire. In the ASD Group, however, no similarity was observed in relation to the composition and acquisition of occupations in the repertoire considering the age of the children. The study made it possible to infer that functional impairment in some areas of development does not prevent children from engaging and participating in meaningful occupations.